Implementasi Prinsip Restorative Justice Tindak Pidana Penganiayaan Pada Tingkat Penyidikan (Studi Kasus Di Polresta Surakarta) - Anindita Ektya Putri, Afina; Fitriciada Azhari, Aidul (UNES Law Review, 2024)
This research aims to examine and analyze the implementation of restorative justice for cases of assault in the Surakarta City Police, as well as the factors that hinder its effectiveness. The methodological approach utilized is socio-legal, with a descriptive-analytical specification. Data sources consist of both primary and secondary data, gathered through interviews and document studies. Data analysis is conducted using qualitative analysis methods. The implementation of restorative justice for assault cases in the Surakarta City Police employs the Family and Community Group Conference model, involving families and community figures to reach comprehensive agreements. This formally refers to regulations such as Article 16 paragraph (1) letter L of Law No. 2 of 2002 regarding the Indonesian National Police, Article 69 letter b of National Police Chief Regulation No. 14/2012 concerning Investigation Management, and National Police Chief Regulation No. 8 of 2021 concerning Handling of Criminal Acts Based on Restorative Justice. Investigators take into consideration several aspects, including the belief that restorative justice is beneficial due to its win-win solutions principle and quick resolutions, prioritizing the principles of utility and legal fairness, as well as providing substantial understanding of law enforcement efforts that guide society. Factors hindering the implementation of restorative justice for assault cases in the Surakarta City Police include the conditions and motivations of involved parties, public unawareness of the authority of restorative justice by investigators, limited community role as social control, and cultural responses to the law. To address the challenges in implementing restorative justice, there is a need for the utilization of restorative justice within the criminal justice system through regulations governing its implementation at the investigative level.